Higher education students perspective on education management information systems: an initial success model proposal - Martins, José (2019)
As higher education evolves into a multifaceted and complex activity, the incorporation of education management information systems (EMIS) that allows for the production of relevant, organized and structured information, becomes a necessity for both institutions and students. Despite the recognition of this requirement, existing literature does not focus on how EMIS might trigger students' success. With this in mind, an initial proposal of a multi-perspective EMIS success model is presented and a validation on the possible existence of linear correlations between the model contexts is described. Moderate correlations have been detected between the majority of the model contexts and a very strong correlation has been detected between students' satisfaction and the arise of net benefits associated with the use of EMIS.